Pengaruh Rasio Keuangan Terhadap Resiko Financial Distress Perbankan Syariah di Indonesia Dengan Pendekatan Bankometer - Dhefita Sari; Rachma Indrarini (ITB AAS INDONESIA Surakarta, 2020)
This study was conducted to investigate financial distress risk of Sharia Commercial Bank in Indonesia during the 2015-2019 period using Bankometer S-Score and to find out its response to shock of financial ratio. The financial ratio that used in this study are FDR, ROA, Leverage and Size bank. The data is a monthly time-series data from January 2015 until December 2019 obtained through the official sharia banking statistics website from Financial Service Autority (https://www.ojk.go.id). The hypothesis are tested by using the Vector Error Correction Model (VECM) methodology. The result of this study indicate that Sharia Commercial Bank in Indonesia are super sound. The VECM test results show that in the short-term the significant effect on the level of S-Score are ROA and Leverage. Meanwhile, the shock of FDR, ROA, Leverage and Size bank have significant effect on S-Score.